Tiha generacija - Maljevac, Simon (Socialno delo, 2022)
Older gays and lesbians are one of the most invisible social groups as they experience “double invisibility”: in Western societies that celebrate youth, they are invisible as older and as older homo- sexuals. Existing research shows a different structure of social networks of older gays and lesbians compared to older heterosexuals, it points to fears of discrimination in care activities and feelings of exclusion from the LGBT community, which, like society at large, is defined by youth. This explo- ratory study for Slovenia identifies similar trends, with the key problem being the tension between an individual’s stigmatized homosexual identity, which the elderly still mostly hide, and the LGBT community, which is not inclusive for older gays and lesbians. The purpose of the research was to identify key characteristics of everyday life of older gays and lesbians in the period before the existence of activism in Slovenia and the characteristics of the current position of older gays and lesbians in the LGBT community and society at large.
Keywords: aging population; coming out; gay; gej; identiteta; identity; lesbian; lezbijka; LGBT; razkritje; staranje populacije